Improvement of the Water Infrastructure in Central Moldova. (2017) - Dinet, Eduard; Racoviteanu, Gabriel; Jercan, Alexandru
Abstract: Selection of the optimum solution for drinking water supply is very difficult operation, considering the constraints generated by presence of many factors which influence the selection process. In order to select the optimal solution multi-criterial analyses have to be performed, considering technical, institutional, environmental and financial aspects for each analyzed option. Such an analysis was carried out for the development of a water supply system for all localities of two rayons, Calarasi and Straseni, located in the central area of the Republic of Moldova.